The Impact of Teacher Demographic Representation on Student Attendance and Suspensions - Stephen B. Holt; Seth Gershenson (Institute for the Study of Labor (IZA), 2015)
Representative bureaucracy theory is central to public administration scholarship due to the likely relationship between the demographic composition of the public workforce and both the actual and perceived performance of public organizations. Primary school classrooms provide an ideal context in which to test the predictions of representative bureaucracy theory at the micro (student) level. Specifically, since parents have at least some agency over primary school students' daily attendance, absences reflect parental assessments of their child's school, classroom, and teacher. The representativeness of the teacher workforce, and specifically that of the student's classroom teacher, is therefore likely to influence student absenteeism. Similarly, student suspensions reflect students' relationships with their teacher, students' comfort level in the classroom, and teachers' discretion in the referral of misbehavior. These academically and socially important outcomes provide convenient, objective measures of behaviors that are likely influenced by street-level representation. Using longitudinal student-level administrative data from the North Carolina, we use a two-way (student and classroom) fixed effects strategy to identify the impact of student-teacher demographic mismatch on primary school students' absences and suspensions. We find that representation among street-level bureaucrats significantly decreases both absenteeism and suspensions and that these effects can be given a causal interpretation. The introduction of two-way fixed effects estimators to public administration scholarship is a secondary contribution of the current study.
Keywords: I2; 330; representative bureaucracy; student absences; elementary education; teacher workforce